Evaluating the links between intake of milk/dairy products and cancer - Chagas, Carlos E. A. [UNESP]; Rogero, Marcelo M.; Martini, Ligia A. (Wiley-Blackwell, 2012)
Milk and dairy products are widely recommended as part of a healthy diet. These products, however, can contain hormones such as insulin-like growth factor 1, and some studies have suggested that a high intake of milk and dairy products may increase the risk of cancer. This review examines recent studies on this topic, with the evidence suggesting that the recommended intake of milk and dairy products (3 servings/day) is safe and, importantly, does not seem to increase the risk of cancer. on the basis of the studies included in this review, cultured milk, yogurt, and low-fat dairy products should be preferred as the milk and dairy products of choice.
Keywords: dairy; diet; health